Local food systems in public procurement. A comparative law analysis in four European Union Member States - Kapała, Anna; Muñoz Gómez, Marta J. (Przegląd Prawa Rolnego, 2024)
The aim of the considerations is to determine whether and to what extent selected EU Member States – Italy, France, Spain and Poland – have applied legal instruments to promote local food systems through public procurement, and in particular, whether they have provided for the food rooting criterion, or the localism food clause which favours food which is geographically closer, to be applied in the public procurement process. The conducted considerations show that both Italian, French and Spanish legislations have incorporated the localism food clause, though differently in each Member State: in Italy and Spain through regional regulations that explicitly contain such a clause, in France – through the institutionalisation of the Territorial Food Projects. Direct delivery, or even “local” products criteria are also included in the school food regulations of these countries. In Poland, on the contrary, neither the public procurement law nor food school regulations favour local food systems, as they completely ignore the criteria relating to the characteristics of the products related to their origin or delivery method.